Zeaxanthin‐based dietary supplement and topical serum improve hydration and reduce wrinkle count in female subjects. (17th June 2016) - Schwartz, Steve; Frank, Emily; Gierhart, Dennis; Simpson, Paula; Frumento, Robert
Summary: Background: Dietary modification, through supplementation and elimination diets, has become an area of interest to help slow skin aging, reduce symptom severity or prevent reoccurrence of certain dermatologic conditions [Clinical Dermatology vol. 31 (2013) 677–700]. Free radical components (reactive oxygen species or ROS) or lipid peroxide (LPO) is involved in the pathogenesis and progression of accelerated skin aging when prolonged oxidative stress occurs. The use of antioxidant‐related therapies such as nutraceuticals is of particular interest in restoring skin homeostasis. Antioxidant carotenoid zeaxanthin is concentrated in the eye and skin tissue and believed to decrease the formation of ROS associated with UV light exposure. With zeaxanthin, phytoceramides, and botanical extracts an oral and topical test product (with zeaxanthin, algae extracts, peptides, hyaluronate) have been developed to improve the appearance and condition of skin when used as directed. Methods: Subjects were divided into three groups: two tests (skin formula 1 – oral product alone (ZO‐1), skin formula 2‐ oral product with topical product (ZO‐2 + ZT)), and one placebo control. The study consisted of a washout visit, baseline (randomization), week two (2), week four (4), week six (6), week eight (8), and week twelve (12). Key parameters measured were as follows: fine lines, deep lines, total wrinkles, wrinkle severity, radiance/skin color (L, a*, b*), discolorations, and skin pigment homogeneity. Results: Thirty‐one subjects completed the twelve‐week study; no adverse events were recorded during the study. Statistically significant improvements from baseline mean hydration score were observed in active groups at weeks 2, 6, and 8. A statistically significant difference was observed between mean differences from baseline scores for total wrinkle count at week 4 for the combination active groups compared to placebo. A statistically significant difference from baseline scores for fine lines count was also observed at the week 4 visit compared to placebo for both active groups. Statistically significant differences from baseline scores for average wrinkles severity were seen for week 12 visit for both active groups compared to placebo. Conclusion: We have shown that the combination of zeaxanthin‐based dietary supplement plus a topical formulation produces superior hydration to that of placebo. Additionally, we have shown that the combination of oral and topical combination vs . oral alone has superior abilities to improve parameters associated with facial lines and wrinkles compared to placebo, although the dietary supplement alone proved most effective in reducing wrinkle count and severity.